1985
DOI: 10.1099/00221287-131-4-927
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of an R Plasmid from a Cryptic Plasmid by Transposition of Two Copies of Tn1 in Providencia stuartii

Abstract: Examination of a series of isolates of Providencia stuartii collected over an 18 month period from a chronic-care patient at Bristol Royal Infirmary revealed the emergence of resistance to carbenicillin. Resistance was mediated by a 47 kb plasmid which transferred by conjugation to a plasmid-free strain of P. stuartii but not to Escherichia coli. Carbenicillin-sensitive isolates were either plasmid-free or contained a 36 kb cryptic plasmid. Restriction endonuclease mapping of this plasmid showed it to be close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Nevertheless, the formation of new transposon structures is almost never observed directly in clinical or environmental settings, presumably because of the low frequency with which the events occur. The exceptions to this include the observation by Hawkey et al (19) of the probable path of evolution of an R plasmid from a cryptic plasmid in clinical isolates of Providencia stuartii collected over an 18-month period from a single chronic-care patient in the Bristol Royal Infirmary. van der Ploeg et al (49) observed transposition of the class I insertion sequence IS1247 from an unlinked site on the chromosome of Xanthobacter autotrophicus GJ10 to a chromosomal location upstream of the haloacetate dehalogenase gene dhlB.…”
Section: Fig 3 Junction R Dna Sequences Of Pcpe3 and Tn5271mentioning
confidence: 99%
“…Nevertheless, the formation of new transposon structures is almost never observed directly in clinical or environmental settings, presumably because of the low frequency with which the events occur. The exceptions to this include the observation by Hawkey et al (19) of the probable path of evolution of an R plasmid from a cryptic plasmid in clinical isolates of Providencia stuartii collected over an 18-month period from a single chronic-care patient in the Bristol Royal Infirmary. van der Ploeg et al (49) observed transposition of the class I insertion sequence IS1247 from an unlinked site on the chromosome of Xanthobacter autotrophicus GJ10 to a chromosomal location upstream of the haloacetate dehalogenase gene dhlB.…”
Section: Fig 3 Junction R Dna Sequences Of Pcpe3 and Tn5271mentioning
confidence: 99%
“…The laboratory numbers used and strain sources are indicated in Table 1. Further details on three (A627/85, A628/ 85, and A629/85) strains, which were received from P. Hawkey, University of Leeds, Leeds, United Kingdom, have been published previously (11,12). The majority of strains (17 of 26) were isolated from urine specimens, and .0 a All strains were urine isolates except for those marked (w), which were wound swab isolates, or (o), which were isolated from other material (blood or unspecified source).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterialstrains andgrowth conditions. Experiments were done with P. stuartii strains P308 and P306 (Hawkey et al, 1985;Chopra et al, 1987). The latter carries the plasmid pUB2660, which encodes a TEM2-type P-lactamase (Hawkey et al, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were done with P. stuartii strains P308 and P306 (Hawkey et al, 1985;Chopra et al, 1987). The latter carries the plasmid pUB2660, which encodes a TEM2-type P-lactamase (Hawkey et al, 1985). Bacteria were grown aerobically at 37 "C either in a nutrient broth (Lab M broth; London Analytical and Bacteriological Media) or on nutrient agar (Lab M agar; London Analytical and Bacteriological Media).…”
Section: Methodsmentioning
confidence: 99%